If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18g + 7 = 14g + -9 Reorder the terms: 7 + 18g = 14g + -9 Reorder the terms: 7 + 18g = -9 + 14g Solving 7 + 18g = -9 + 14g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-14g' to each side of the equation. 7 + 18g + -14g = -9 + 14g + -14g Combine like terms: 18g + -14g = 4g 7 + 4g = -9 + 14g + -14g Combine like terms: 14g + -14g = 0 7 + 4g = -9 + 0 7 + 4g = -9 Add '-7' to each side of the equation. 7 + -7 + 4g = -9 + -7 Combine like terms: 7 + -7 = 0 0 + 4g = -9 + -7 4g = -9 + -7 Combine like terms: -9 + -7 = -16 4g = -16 Divide each side by '4'. g = -4 Simplifying g = -4
| 8x-12=3x+11 | | =4x^2-5x+12 | | 5a-8a+3a= | | -2d+18-4d=16 | | 2+3y=8 | | 3.3q-2.9-4.8q=2.5q-4.9 | | 6+b=7 | | 15d-8-3d=16 | | (2x^3+3x^2-1)=0 | | (3b-2)(3b^3+6b^2+2)= | | 7x=14+15x | | 4(y+4)=5(y-3) | | 6.7+12m-9.3=6.2 | | 91-3x= | | 2x*4=8 | | 2x^2+2y^2-xy+15x+30=0 | | x-15=-28 | | x^3-6x-16=0 | | (4x+3)(2x-4)= | | p^2-7p=28 | | (4x-1)/6+(2x+1)/2=2 | | 10x-9-9=14x-9+6x | | 15n+15+4n=130 | | x^2+7c+10=0 | | x+12=21 | | 4k^2-125=5k | | 7-k=5+3k | | x^2-8x*7=0 | | (x-y)(x^2+y^2)= | | -5t-14=2n | | ln(2x-3)=0 | | 2p^2-63=11p |